A Study on the Ethanolic Extracts of Red Seaweed- Gracilaria corticata (J.Agardh) J. Agardh, to Assess the Antiproliferative Activity and Morphological Characterization of Apoptosis on HeLa Cell lines - Ashwini S; Manjula Shantaram (International Journal of Phytomedicine, 2017)
Marine algae are excellent source of bioactive compounds that can be used as an alternative source for finding novel anti-cancer molecules. Gracilaria corticata, red algae from Surathkal beach, Karnataka were studied for their anti-proliferative activities and their morphological characterization on HeLa cells were assessed. Cytotoxicity of the algal ethanolic extracts on HeLa cells were assayed by 3-(4,5-dimethylthiazol-2-yl)-2, 5- diphenyltetrazolium bromide (MTT) reduction method. Morphological assessment was done by examinations with Hoechst staining and acid vacuoles were determined using acridine orange. Induction of apoptosis was studied using caspase activity. Based on IC50value, further morphological assessment was carried out and apoptosis was confirmed using Hoechst 33342 staining and acridine orange staining respectively. Treated cells became round with blebbings with condensed nuclei. Acidic lysosomal vacuoles formation occurred in treated cells. These red algae were able to suppress proliferation and promote apoptosis– mediated cell death with induction of initial stages of apoptosis in HeLa cell lines. Thus, this seaweed can be a potent candidate for isolating new green drug anticancer molecules. However, further characterization at the molecular and structural levels are required.